The Use of Conceptual Metaphors in the Translation of Kitab Al-Hikam by D.A. Pakih Sati by Ibn ‘Aṭāillah Al-Sakandarī - Suparno, Darsita; Muhamad Rohman, Rizal; Maulani, Abdullah; Hifni, Achmad; Helmanita, Karlina; Attih, Driss (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This research aims to analyze the use of conceptual metaphors in the translation of Al-Hikam by D.A. Pakih Sati, originally written by Ibn â€˜Aá¹Äillah Al-SakandarÄ«. The method used is descriptive qualitative to identify and classify conceptual metaphors based on the theory of Lakoff and Johnson. The research data consists of twenty-one conceptual metaphors divided into three main types: 13 ontological metaphors, 5 structural metaphors, and 3 orientational metaphors. The results of the analysis show the dominance of ontological metaphors in this translation, which conceptualize experiences and processes in metaphorical language relying on pre-conceptualized meanings in the mind. The implications of this research provide a deeper understanding of how conceptual metaphors are used in the context of translating spiritual texts, as well as their contribution to the comprehension and interpretation of classical texts in religious culture.